Penerapan Model Pembelajaran Kooperatif Tipe Role Playing untuk Meningkatkan Hasil Belajar Pendidikan Pancasila Siswa Kelas IV - Hakim, Abdul; Usman, Usman; Suhrawardiah, Suhrawardiah (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
This research aims to determine the improvement of student learning processes and outcomes through the application of the Role Playing Type Cooperative Learning Model. This research uses a qualitative approach with the type of Classroom Action Research (PTK). The data collection techniques used are observation, tests and documentation. The research was carried out in three cycles, each consisting of one meeting. The results of the research show that the learning process and student learning outcomes have increased, in cycle 1, the learning process in teacher activities reached the fair  qualification (C) while the student learning process and outcomes reached the Poor qualification (K). In cycle II the learning process in teacher activities achieved Good qualifications (B) while the student learning processes and outcomes achieved Fair qualifications (C). In cycle III the learning process in teacher and student activities and student learning outcomes achieved Good (B) qualifications. The conclusion of this research is that the application of the Role Playing Type Cooperative learning model can improve the learning process and outcomes of Pancasila Education for class IV UPTD students at SD Negeri 79 Parepare